Perfil clínico-epidemiológico de pacientes internados por COVID-19 em duas unidades de saúde na região do Jequitinhonha – Minas Gerais – no ano de 2020 - Moreira, Bárbara Lopes; Matos, Paola Martins De; Oliveira, Maria Clara de Moura; Lima, Vanessa Pereira; Santos, Ana Paula (Revista Vozes dos Vales: Publicações Acadêmicas, 2024)
COVID-19 became, in January 2020, a public health emergency of international importance, being responsible for many hospitalizations and deaths. This study aimed to analyze the clinical-epidemiological profile of individuals hospitalized for COVID-19 in two health units in the Jequitinhonha macro-region in 2020. Descriptive observational study, with data review of medical records of all patients diagnosed with COVID-19 admitted to the Macro Jequitinhonha Diamantina Emergency Unit and Santa Casa de Caridade de Diamantina, in the period between 03/16/2020 (first hospitalized case) and 12/31/2020. Data regarding sociodemographic and clinical characterization were collected. 127 medical records were analyzed, 52% of patients were female, 78.8% were over 50 years old, 75% were brown race, 45% had low education. Admissions were predominantly through the Unified Health System (SUS) (91.4%), the majority of admissions (81%) were of individuals not resident in the municipality of Diamantina and 86.6% were from urban areas. The main pre-existing diseases were: systemic arterial hypertension (58%); diabetes mellitus (25%); obesity (21%) and heart disease (17%). The average number of days of hospitalization was 9.6 ± 7.7; during hospitalization, 87.4% and 40.2% of patients used oxygen therapy and mechanical ventilation, respectively; 37.8% required admission to an intensive care unit; 7.9% were readmitted; and 23.6% of hospitalized patients died. The individuals hospitalized in the Jequitinhonha Diamantina macro-region, in the period analyzed, were admitted predominantly by the SUS, the majority were over 50 years old, from the urban area in the Diamantina region and the mortality rate was 23.6%.
Keywords: Coronavirus Infections; Pandemics; Epidemiology; Electronic Health Records